COMPARISON OF METFORMIN VS REGULAR INSULIN IN THE MANAGEMENT OF PATIENTS WITH GESTATIONAL DIABETES MELLITUS (The Research of Medical Science Review, 2025)
Background: Gestational diabetes mellitus (GDM) is a relatively frequent type of diabetes that complicates about 1-14% of all pregnancies. Although insulin remains the most frequently used treatment method in GDM, metformin could be useful because of its simple administration and low cost. The effectiveness, side effects, and results of metformin and regular insulin as a treatment in GDM are evaluated in this research. Aim: To assess and to compare the effectiveness of metformin and regular insulin on glycemic control, maternal and fetal outcomes, and safety profile. Methods: This was a randomized controlled trial that enrolled 200 pregnant women diagnosed with GDM either by ADA or WHO criteria. Participants were divided into two groups: Metformin with lifestyle changes was given to Group A and Regular insulin to Group B. Maternal indices including age, parity, gestational age, BMI pre-pregnancy, smoking history and pre-existing medical conditions, maternal complications and fetal macrosomia and neonatal hypoglycaemia as well as glycemic control indices such as pre and postprandial glucose and HbA1c at the time of booking were compared between the two groups. t-Tests and chi-square tests were conducted to assess differences and logistic regression for outcome predictors. Results: Metformin and insulin were similarly effective with the fasting glucose of 90.5 ± 5.3 mg/dL in the metformin group and 91.8 ± 5.9 mg/dL in the insulin group. Patients in both groups attained hoped for target HbA1c level in 82% and 85% of metformin and insulin respectively. Metformin was associated with less maternal weight gain (15%) and a lower caesarean delivery rate of 25% compared with 20% and 30% for insulin. Of neonatal features they were similar in both groups regarding birth weight and macrosomia but the frequency ofhypoglycaemia in the neonate in the metformin’s group was 7% and insulin group was 5%. Gastrointestinal complaints were noted in 0-15% of patients treated with metformin and hypoglycaemia in a 0-12% of the insulin-using subjects. Conclusion: It is for this reason that metformin provides similar glucose control in GDM compared with insulin while at the same time providing additional advantages such as reduced maternal weight gain, fewer caesarean sections and treatment compliance was better in patients on metformin. Hypoglycaemia, specifically neonatal hypoglycaemia and the overall long-term impact of metformin in pregnancy require further investigation, metformin has been identified to be an ideal additional or substitute to insulin. Proper treatment in the future should consider the client/case characteristics and thereafter establish a controlled follow- up.